Characteristics and enhanced antioxidant activity of glycated Morchella esculenta protein isolate - ZHANG,Qiang (2018)
Abstract Morchella esculenta (L) Pers. is a highly valued edible and medicinal fungus that remains underutilized. For this study, the effects of glycation treatment on antioxidant activity and characteristics of the M. esculenta protein isolate (MPI) were investigated via the Maillard reaction. Conjugation between MPI and xylose was proven via UV-vis, FT-IR, intrinsic fluorescence analysis, and SDS-PAGE. Amino acid analysis revealed involvement of lysine, arginine and tyrosine in MPI, forming a covalent cross-link with xylose. Differential scanning calorimetry (DSC) results showed that glycated MPI (MPIG) possesses a more favorable thermal stability compared to native MPI (MPIN), heated MPI (MPIH) and an unheated mixture of MPI and xylose (MPI-XM). MPIG exhibited significantly enhanced antioxidant activity compared to MPIN, MPIH, and MPI-XM. These results indicate MPIG can serve as a promising novel source of nutraceutical and functional ingredients that exert antioxidant activity.